PENGGUNAAN MEDIA KARTU UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB PESERTA DIDIK KELAS VII E MTsN 4 SIDOARJO TAHUN PELAJARAN 2019-2020 - Nur Sjamsuarini Pudji Astutik (Madaris: Jurnal Guru Inovatif, 2021)
The purpose of this study was to obtain a series of information / data about the Arabic language learning process which included: (1) Implementation of the use of card media in class VII E MTsN 4 Sidoarjo students, (2) The role of card media to improve Arabic learning activities for grade VII students. E MTsN 4 Sidoarjo, (3) The role of media cards to improve Arabic learning outcomes for class VII E MTsN 4 Sidoarjo students, (4) Student responses to card media. This type of research is a classroom action research conducted in four cycles. The subjects of this study were 34 students of class VII E in the first semester of the 2019-2020 school year. The data collected includes, teacher and student activity data collected through observation using observation sheets, cognitive learning outcome data collected using objective tests and student response data to card media collected using a questionnaire. The indicator of success in this study is if classically 85% of the students' learning outcomes test reaches a score of 75, according to the minimum completeness category (KKM) that applies at MTsN 4 Sidoarjo. Successful indicators of learning outcomes in the affective domain, if 80% of students reach the "good" category. Indicators of the success of student responses to card media, if 80% of students reach the "good" category, while for teacher activities it is said to be successful if they have carried out learning activities in the "very good" category. The results showed that (1) the learning that was carried out by the teacher could run very well, cyclically the results of the intervention in each cycle were used for the next cycle, and the deficiencies in each cycle could be corrected in the next cycle, (2) Observation of student activity for affective assessment , increased, and had met the KKM. Thus optimizing the use of card media can improve Arabic learning outcomes in the Basic Competence of understanding At-Ta'aruf (introduction), (4) Students' responses to the card media used are considered very good on each indicator. Students become unsaturated, and it is easier to understand the material.